(untitled) (Bangladesh Journal of Zoology, 2018)
Oviposition preference and development of rice weevil, Sitophilus oryzae (Coleoptera: Curculionidae) were observed in three varieties of stored grains i.e. parboiled rice (Oryza sativa), wheat (Triticum aestivum) and pulse (Cicer arietinum). In no choice tests, the mean number of eggs laid were 360.3 ±2.60 in rice, 382 ±2.49 in wheat and 394± 2.06 in pulse. In case of choice tests, the mean number of eggs laid were 13.6±0.4 in rice, 14.2 ±0.37 in wheat and 15.6 ±0.4 in pulse. The differences between the number of eggs laid in rice, wheat and pulse varied significantly in both no-choice and choice tests. The respective incubation period, larval and pupal period of the weevil reared on rice, wheat and pulse were 5.7 ±0.27, 5 ±0.47 and 5.4 ±0.27 days, respectively, 21 ±0.47, 20.3 ± 0.27, 19 ±0.47 days, respectively and 10.3 ±0.27, 10.7 ±0.27, 11.3 ±0.27 days, respectively. The total development time from egg to adult recorded in rice, wheat and pulse was 37 ±0.47, 36 ±0.47 and 35.6 ±0.72 days, respectively. The difference between the larval periods was significant (p < 0.05) when they reared in wheat and pulse. The larval and pupal period varied significantly (p < 0.05) between the individuals reared in rice and pulse. The developmental period was shorter in pulse than in rice and wheat. Bangladesh J. Zool. 45(2): 131-138, 2017